BRIEFING AND DEBRIEFING IN FACILITATING SURGICAL WARD ROUNDS EFFICIENCY - Dr. Tarkeshwar Kumar; Manoj Kumar (Student's Journal of Health Research, 2023)
Background:  It has been observed that the application of briefing and debriefing protocols has proven to be effective when it comes to surgical protocols. Here, an attempt is made to apply the protocol to running a surgical ward. Surgical ward rounds are an important part of treatment for surgical patients, and using briefing and debriefing protocols can make it more efficient and reliable. Methods:  This study is prospective observational conducted over 40 days. A systematic protocol was established to conduct a briefing before the surgical ward round and a debriefing after the surgical ward round. Predetermined objectives were set to be achieved during the briefing and debriefing sessions. Feedback from the ward round members was taken, and observations were analyzed. Results:  Feedback obtained from the surgical ward round members was positive, with improvement in the working environment of the healthcare professionals, learning outcomes improved in juniors and medical students, and healthcare services provided to the patients also improved significantly. Conclusion:  Briefing and debriefing protocol can significantly impact and play a positive role in improving the efficiency of surgical ward rounds and thus ensure better healthcare services are provided after the surgery.